2008
DOI: 10.1074/jbc.m804271200
|View full text |Cite
|
Sign up to set email alerts
|

Significance of NF-κB/GATA Axis in Tumor Necrosis Factor-α-induced Expression of 6-Sulfated Cell Recognition Glycans in Human T-lymphocytes

Abstract: Sulfated glycans play critical roles in various cell recognition events among leukocytes. The 6-sulfated lactosamine glycans in particular have been widely noted for their importance because they are involved in cell recognition events mediated by celladhesion molecules such as selectins and sialic acid-recognizing molecules such as siglecs and also in the activation of CD44 in binding to extracellular matrix hyaluronate. A pro-inflammatory cytokine, tumor necrosis factor-␣, induces expression of 6-sulfated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
(41 reference statements)
2
8
0
Order By: Relevance
“…Clarithromycin also reduced NF-B proteins induced by influenza virus infection. These findings are consistent with those reported previously (Delmotte et al, 2002;Suzuki et al, 2002;Yasukawa et al, 2005;Chen et al, 2008). Clarithromycin might reduce the expression of SA␣2,6Gal on the cells partly through the reduction of NF-B activation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Clarithromycin also reduced NF-B proteins induced by influenza virus infection. These findings are consistent with those reported previously (Delmotte et al, 2002;Suzuki et al, 2002;Yasukawa et al, 2005;Chen et al, 2008). Clarithromycin might reduce the expression of SA␣2,6Gal on the cells partly through the reduction of NF-B activation.…”
Section: Discussionsupporting
confidence: 83%
“…However, tumor necrosis factor-␣, one of inflammatory mediators in airways, increases the expression glycosyltransferase and sulfotransferase responsible for biosynthesis of sialylated epitopes in the bronchial mucosa (Delmotte et al, 2002), through the activation of NF-B (Chen et al, 2008). ␣2,6-Sialic acid in glycoproteins also increases in inflamed mouse serum in response to turpentine oil (Yasukawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…38,39 In another example, nuclear factor-B (NF-B) is known to be activated by T-cell receptor engagement, and activation of important downstream target genes, such as GlNAc6ST-1, a gene that encodes a sulfotransferase required for the synthesis of 6-sulfated cell recognition glycans, is dependent on physical interaction with GATA-3. 40 Das et al have also shown that in NF-B p50-deficient mice, CD4 ϩ T cells failed to induce GATA-3 expression under Th2 priming condition but maintained unimpaired T-bet and IFN-␥ expression under Th1 differentiation conditions. 41 These reports initially suggested the possibility that a c-Myb/GATA-3 coactivator complex might include Smad3 or NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…Adjacent κB and GATA sites have been identified in many insect immune gene promoters and both sites are required for gene induction (Harshman and James, 1998; Kadalayil et al, 1997; Senger et al, 2004; Tingvall et al, 2001). Human GATA-3 and/or GATA-2 interact with NF-κB to trigger GlcNac6ST-1 transcription (Chen et al, 2008). In addition, κB and GATA sites are both required for induced expression of Drosophila cecropin A (Kadalayil et al, 1997).…”
Section: Introductionmentioning
confidence: 99%